FAILURE TO THRIVE (FTT) IN INFANTS: AN EVIDENCE-BASED REVIEW OF CAUSES AND MANAGEMENT - Ewa Romanowicz; Hanna Skarakhodava; Agnieszka Floriańczyk; Aleksandra Kołdyj; Agnieszka Ozdarska; Adrian Krzysztof Biernat; Marcin Lampart; Anna Rupińska; Kamila Krzewska (International Journal of Innovative Technologies in Social Science, 2025)
Failure to thrive (FTT) in infancy is a multifactorial condition characterized by inadequate physical growth due to medical, nutritional, or psychosocial factors. This review explores the underlying causes and evidence-based strategies for diagnosis and management of FTT in infants. Drawing from clinical guidelines and recent studies, the article emphasizes the need for accurate anthropometric assessment using standardized growth charts and z-scores. FTT is commonly classified as either organic, linked to identifiable medical conditions, or non-organic, often associated with environmental stressors or inadequate caregiving practices. Comprehensive clinical evaluation, including detailed history-taking, physical examination, and recognition of red-flag symptoms, is essential for early detection. Management requires individualized nutritional rehabilitation, treatment of underlying medical issues, and psychosocial support involving multidisciplinary teams. Early, targeted intervention is associated with improved outcomes in growth, cognition, and emotional development. Standardized diagnostic criteria, coordinated care plans, and caregiver support are critical for mitigating the long-term consequences of growth faltering and optimizing developmental trajectories in this vulnerable population.